Over 80% of Africa's savannah conservation land is failing or deteriorating according to lions as an indicator species. Issue 1 (6th December 2021) - Robson, Ashley; Trimble, Morgan; Bauer, Dominik; Loveridge, Andrew; Thomson, Paul; Western, Guy; Lindsey, Peter
Abstract: Calls to increase the global area under protection for conservation assume existing conservation areas are effective but, without adequate investment, they may not be. We collected survey data from expert respondents on perceived budgets, management, and threats for 516 protected areas and community conservation areas in savannah Africa to create a Conservation Area Performance Index. Combining this index with an indicative biodiversity outcome—population status of African lion, Panthera leo —we found that 82% of the sampled area was in a state of failure or deterioration, with only 10% in a state of success or recovery. A large proportion of succeeding or recovering conservation areas received external support through collaborative management partnerships. That Africa's current conservation area network—the foundation of conservation efforts—is crumbling complicates proposed strategies to protect additional land. We contend that investing in the effective management of existing conservation areas—potentially through well‐structured collaborative management partnerships—should be prioritized urgently.